The implementation of Padlet in teaching writing skills of recount text for eighth grade students in Bandung - Hidayat, Reby Saharra; Satriani, Intan (ELT in Focus, 2023)
Nowadays, teachers need interesting media to facilitate teaching and learning process in the classroom. So, Padlet is one of media needed in teaching writing skill of recount text. This research aimed at finding out the implementation of Padlet in teaching writing to eight grade students of junior high school in Bandung. This research used case study research design as the methodology. The participants of this research were 33 seventh grade students at one of junior high school in Bandung. This research applied observation sheet as the research instrument. Based on the results obtained, the implementation of writing recount text using Padlet was successful in gaining the students’ involvement in writing recount text, students’ problem solving without teachers’ help and students’ understanding of instructions in each meeting. In conclusion, the implementation of Padlet really supports learning writing skills, especially for recount text.